2006
DOI: 10.1038/modpathol.3800643
|View full text |Cite
|
Sign up to set email alerts
|

Biliary cystic tumors with bile duct communication: a cystic variant of intraductal papillary neoplasm of the bile duct

Abstract: Biliary cystic tumors, which are also called biliary cystadenoma and cystadenocarcinoma, are thought to be a heterogeneous disease entity, and some of them are known to show a luminal communication to the bile duct. In this study, we examined the clinicopathological features of nine cases of biliary cystic tumors with bile duct communication. They were composed of five males and four females with an average age of 67 years (52-84 years). They were multilocular (eight cases) or unilocular (one case), and all ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
153
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 155 publications
(165 citation statements)
references
References 25 publications
10
153
0
2
Order By: Relevance
“…6–19 No systemic review was included. Except for one article,15 all of the remaining articles were case reports. One article described biliary cystic tumors, and included two cases of mucinous cholangiocarcinoma 15.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…6–19 No systemic review was included. Except for one article,15 all of the remaining articles were case reports. One article described biliary cystic tumors, and included two cases of mucinous cholangiocarcinoma 15.…”
Section: Resultsmentioning
confidence: 99%
“…Except for one article,15 all of the remaining articles were case reports. One article described biliary cystic tumors, and included two cases of mucinous cholangiocarcinoma 15. Finally, comprehensive data on 16 cases of mucinous cholangiocarcnoma, which included the case treated in our institution, were gathered.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…4 A previous study revealed that cystic liver tumours with bile duct communication share characteristics with intraductal papillary neoplasms, but not mucinous cystic neoplasms. 5 There had been controversy regarding the distinction between mucinous cystic neoplasms and intraductal papillary neoplasms until the presence of an ovarian-like stroma was accepted as a prerequisite for the diagnosis of mucinous cystic neoplasms and the distinct entity of biliary intraductal papillary neoplasms was proposed. Most studies to date have likely examined both types of cystic tumours under a single tumour entity.…”
mentioning
confidence: 99%